PENGARUH PEMBANGUNAN INFRASTRUKTUR JALAN RAYA DAN LISTRIK TERHADAP PDRB DI KOTA MOJOKERTO - Dhimas Ilham Prasetya; Ida Nuraini; Hendra Kusuma (Jurnal Ilmu Ekonomi, 2021)
The purpose of this research is to know the effect of road condition,electricity on PDRB in Mojokerto City. . The method used is a quantitative approach using secondary data obtained from the annual report of BPS of Mojokerto City. The analytical tool used is multiple linear regression. Data was processed through E-views. The results showed that road condition variable and electricity variable have a significant positive effect on PDRB of Mojokerto City. In this study researchers have limitations using only 16 years and using road condition variable and electricity variable as an independent variable so that it can affect theresearch results. The next researcher is expected to beable to develop the number of variables and be able to add observation time.